2016
DOI: 10.3390/app6110333
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory Polymer Composites of Poly(styrene-b-butadiene-b-styrene) Copolymer/Liner Low Density Polyethylene/Fe3O4 Nanoparticles for Remote Activation

Abstract: Magnetically sensitive shape memory poly(styrene-b-butadiene-b-styrene) copolymer (SBS)/liner low density polyethylene (LLDPE) composites filled with various contents of Fe 3 O 4 nanoparticles were prepared. The influence of the Fe 3 O 4 nanoparticles content on the thermal properties, mechanical properties, fracture morphology, magnetic behavior, and shape memory effect of SBS/LLDPE/Fe 3 O 4 composites was systematically studied in this paper. The results indicated that homogeneously dispersed Fe 3 O 4 nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…It was demonstrated that Fe 3 O 4 @Dye-Pol displayed lower cytotoxicity than Fe 3 O 4 nanoparticles, and could be used to label cancer cells for NIR fluorescence microscopy and enhance negative contrast for T2-weighted MR imaging. In addition, Fe 3 O 4 nanoparticles can also be used to design shape memory materials to achieve a fast shape recovery under a magnetic field [ 34 ].…”
Section: Classification Of Supramolecular Polymer Nanocompositesmentioning
confidence: 99%
“…It was demonstrated that Fe 3 O 4 @Dye-Pol displayed lower cytotoxicity than Fe 3 O 4 nanoparticles, and could be used to label cancer cells for NIR fluorescence microscopy and enhance negative contrast for T2-weighted MR imaging. In addition, Fe 3 O 4 nanoparticles can also be used to design shape memory materials to achieve a fast shape recovery under a magnetic field [ 34 ].…”
Section: Classification Of Supramolecular Polymer Nanocompositesmentioning
confidence: 99%
“…carbon nanotubes, carbon nanofibers, exfoliated nanoclay…, to improve the mechanical performance of the resulting material, called shape memory polymer composites (SMPC) [ 78 ]. They could also include Fe 3 O 4 -particles, or other magnetizable materials in order to make them magneto-responsive [ 79 , 80 ].…”
Section: Active Control In Other Fieldsmentioning
confidence: 99%
“…At present, shape memory polymers have been applied in many fields such as aerospace [ 6 ], medicine [ 7 , 8 ], self-finishing smart textiles [ 9 ], electronic devices [ 10 ], and self-assembling structures [ 11 ]. Various types of polymers have been found to have shape memory effects including polyurethane [ 12 , 13 ], trans-polyisoprene [ 14 ], styrene-butadiene copolymer [ 15 ], and epoxy material [ 16 ].…”
Section: Introductionmentioning
confidence: 99%